Analisis Kesalahan Newman Masalah Matematika Kontekstual Persegi Panjang Siswa SMP N 10 Kotabumi - Fhela Vhantoria Ningrum; Ellysia Wahyuni; Muinah (Universitas Cokroaminoto Palopo, 2024)
The research aims to describe Newman's errors in rectangular contextual mathematics problems for students at SMP N 10 Kotabumi. This type of qualitative research is a descriptive case study. Sampling used snowball sampling which then selected 2 students who were grouped into high, medium, and low categories. Data collection techniques use tests and interviews. The instrument is a contextual rectangular test and an interview guide. The results of this research are 1) Students in the high category tend to make errors in the transformation, solving process, and determining the final answer. However, one of the students in the high category made an error in understanding because he made a mistake in determining what was known and was asked, 2) students in the medium category tended to make errors in understanding, transformation, the completion process, and determining the final answer. However, one of the medium category students made a reading error because they read the question incorrectly so it was included in the indicator of not being able to extract keywords and important information from the question, and 3) students in the low category tended to make errors in understanding, transformation, completion process, and determining the final answer. However, one of the low-category students made a reading error because the student did not understand the question he was reading. Reading errors can be seen when students incorrectly determine what is known (field size) and ask questions, make incorrect formulas, and calculate incorrectly